Highly Enantioselective Three-Component Reactions of tert-Butyl Diazoacetate with Arylamines and Imines: An Efficient Synthesis of α,β-Bis(arylamino) Acid Derivatives - Jiang, Liqin; Zhang, Dan; Wang, Zhongqing; Hu, Wenhao (Synthesis, 2013)
Enantioselective three-component reactions of tert-butyl diazoacetate with arylamines and imines afford α,β-bis(arylamino) acid derivatives in good yields (56–90%) with high diastereoselectivities (up to >95:5 dr) and excellent enantioselectivities (up to 96% ee).
Keywords: multicomponent reaction; tert-butyl diazoacetate; ammonium ylide; imine addition; α,β-diamino acids